Analysis of Views of Turkestan EnlightenmentJadids on Perfect Human Education - Amridinova Dilrabo Tursunovna (Peerian Journals Publishing, 2022)
The article describes the scientific-educational heritage of the representatives of the enlightened-jadid movement of Turkestan, its scientific and educational role in the spiritual and moral development of young people, and the importance of the heritage of jadidisms in protecting young people from negative vices such as "spiritual poverty" and "moral depravity".
Keywords: Enlightenment; modernity; Turkestan; knowledge